Delaying gratification depends on social trust - Michaelson, Laura; de la Vega, Alejandro; Chatham, Christopher; Munakata, Yuko (Frontiers in Psychology, 2013)
Delaying gratification is hard, yet predictive of important life outcomes, such as academic achievement and physical health. Prominent theories focus on the role of self-control, hypersensitivity to immediate rewards, and the cost of time spent waiting. However, delaying gratification may also require trust in people delivering future rewards as promised. To test the role of social trust, participants were presented with character vignettes and faces that varied in trustworthiness, and then chose between hypothetical smaller immediate or larger delayed rewards from those characters. Across two experiments, participants were less willing to wait for delayed rewards from less trustworthy characters, and perceived trustworthiness predicted willingness to delay gratification. These findings provide the first demonstration of a causal role for social trust in willingness to delay gratification, independent of other relevant factors, such as self-control or reward history. Thus, delaying gratification requires choosing not only a later reward, but a reward that is potentially less likely to be delivered, when there is doubt about the person promising it. Implications of this work include the need to revise prominent theories of delay of gratification, and new directions for interventions with populations characterized by impulsivity.